VALIDITAS PENGEMBANGAN STRATEGI PEMBELAJARAN PPDP PADA MATERI FOTOSINTESIS UNTUK MENINGKATKAN HASIL BELAJAR KELAS XII SMA DI KOTA PALEMBANG - Ulfa, Khalida (Bioilmi: Jurnal Pendidikan, 2020)
Photosynthetic topic is abstract and complex topic that is interconnected with other topics, causing students to experience difficulties in learning and understanding them. One effort that can be done is to develop PPDP learning strategies. This study aims to produce a learning strategy that can teach concepts through facts, activate students, and can direct students in thinking and reasoning. In developing learning strategies using the Rowntree development model while the assessment or evaluation stage uses the Tessmer model. Data collection instruments in this study were component validation sheets and lesson plans, photosynthetic guideline validation sheets and photosynthetic worksheet and practicality questionnaire in the form of teacher and student responses. Data were analyzed descriptively by presenting results obtained in the field. The results of this study indicate that the development of learning strategies is very valid. That is, this learning strategy has good quality based on expert judgment on the components and content of lesson plans, content, display and language of practicum and LKPD guidelines. By using PPDP learning strategies, it is expected to be able to direct students in active, fun learning, and be able to describe facts or phenomena from photosynthesis.